Gag reflex management in dental practice: a bibliometric analysis from 2000 to 2025 - Gan, Yena; Huang, Jinwei; Li, Duoduo; Xu, He; Han, Sheng; Zhu, He; Wei, Zening; Cai, Zhigang (Frontiers in Oral Health, 2025)
BackgroundThe gag reflex is a common challenge in dental practice, often causing discomfort and leading to treatment avoidance, especially during procedures like taking dental impressions. Although both pharmacological and non-pharmacological treatments are utilized to manage the gag reflex, current evidence supporting the routine use of these interventions is limited, highlighting the need for further research. To optimize gag reflex management and identify future research trends through a bibliometric analysis.MethodsData from eligible studies were extracted through a comprehensive search and various analyses, including descriptive bibliometric, citation, keyword, and thematic analyses. Group comparisons were made between Asian and non-Asian groups to assess the differences and trends between the two regions.ResultsBetween 2000 and 2025, 47 studies were published, with an average annual increase of 4.68%. Japan, Iran, India, the USA, and Turkey each contributed at least 10 studies, and studies from Lebanon had the highest citation frequency. The majority of studies were randomized controlled trials (46.81%), followed by case reports (46.81%) and case series (6.38%). Most studies (80.85%) focused on adults undergoing extractions (38.30%), restorations (31.91%), and dental impressions (14.89%). Interventions primarily targeted nausea and vomiting (74.47%) using pharmacological treatments such as lidocaine, propofol, and midazolam and non-pharmacological methods such as acupuncture, acupressure, and Transcutaneous Electrical Nerve Stimulation. Significant differences were observed between Asian and non-Asian groups in publication years, study designs, demographics, treatments, and clinical outcomes.ConclusionsGag reflex management has advanced with pharmacological treatments for immediate relief and increased use of non-pharmacological methods such as acupuncture and laser stimulation, particularly in Japan, Turkey, and the USA. However, challenges such as small-scale studies, limited follow-ups, and underrepresentation of children and adolescents highlight the need for larger studies, standardized tools, and inclusive approaches for diverse patient groups.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250650382, identifier (CRD420250650382).